Effect of degree of octenyl succinic anhydride (OSA) substitution on the digestion of emulsions and the bioaccessibility of β-carotene in OSA-modified-starch-stabilized-emulsions. (November 2018) - Lin, Quanquan; Liang, Rong; Zhong, Fang; Ye, Aiqian; Singh, Harjinder
Abstract: The degree of substitution (DS) is one of the most important properties of octenyl succinic anhydride (OSA)-modified starch, in terms of optimizing its functionality in the application of delivery systems for lipophilic bioactive components. This study investigated the effect of the DS of OSA-modified starch on the in vitro digestion behavior and the β-carotene bioaccessibility in nanoemulsions stabilized by OSA-modified starches. Changes in the particle size and distribution, microstructure, zeta-potential, hydrolysis of the starch, and lipolysis in the emulsions during digestion as well as the bioaccessibility of β-carotene were determined. All the emulsions remained stable during the mouth stage and their particle size increased significantly after incubation under gastric conditions, with the extent of increase in the particle size being negatively correlated to the DS. Under gastric conditions, the emulsions stabilized by OSA-modified starches with higher DS values had less flocculation and coalescence, which could probably be attributed to the greater steric hindrance of branched amylopectin chains and the greater magnitudes of the negative zeta-potential in the presence of more OSA groups. The more rigid and compact surface structure formed by the OSA-modified starch with higher DS provide better protection against the biochemical conditions in the gastric fluid. When the DS increased from 0.0158 to 0.0416, the bioaccessibility of β-carotene was enhanced from 8.01 ± 0.88 to 20.39 ± 1.93%, which may have been due to a lower extent of starch digestion and a greater extent of lipid digestion in nanoemulsions stabilized by OSA-modified starch with higher DS values. Graphical abstract: Image 1 Highlights: Stable β-carotene nanoemulsions were prepared using lab-made OSA-modified starch. Greater DS led to less droplet flocculation and coalescence in the gastric phase. Greater DS resulted in a lower rate and a lesser extent of starch digestion. Greater DS led to a higher rate and a greater extent of lipid digestion. Greater DS contributed to higher bioaccessibility of β-carotene in nanoemulsions.